The Moral Context of the Prohibition of Riba in Islam Revisited - Abdullah Saeed (International Institute of Islamic Thought, 1995)
The prohibition of riba (interest) in Islam has been a hotly discussed issue among contemporary Muslims since the 1960s. Since rihd is perceived by a considerable number of Muslims to be bank interest, and almost all banking systems in the world, including those of the Muslim world, are based on interest, many Muslims are concerned whether it is lawful. For those who regard bank interest as rihd, any increase in a loan transaction over and above the principal is rihd because it involves an increase over and above the principal. They contend that the fiqhi interpretation of riba is the interpretation and must be followed. For other Muslims, the prohibition of riba is related closely to the “exploitation” of the needy and poor by the relatively well-off, an element that, for them, may or may not exist in modem bank interest. These Muslims have argued that the fiqhi interpretation given to riha is inadequate and does not take into consideration the moral emphasis associated with the prohibition. This paper looks at a) the overall context of the Qur’anic prohibition of rihd; b) how the term is used in the Qur’an, the Sunnah, and in thefiqhl literature; and c) the lack of moral emphasis in the current debate. Riba and the Qur’an: The Context of Prohibition The Qur’an’s condemnation and ultimate prohibition of riba was preceded by its condemnation of several other morally unacceptable forms of behavior toward the socially and economically weaker strata of the Makkan community. From the very beginning of the Prophet’s mission, ...